Unusual Presentation of Prostate Cancer Metastatic to the Cricoid Cartilage and Oral Cavity - Marlene Olvera; Miriam Delgado; Melchor Vázquez; José Zavala; Verónica Macedo; Martha Puentes (Case Reports in Medicine)
In Mexico, prostate cancer is the second leading cause of death in men. Prostate cancer usually presents metastasis to the regional lymph nodes and bone. Hereby, we present an unusual case of metastatic prostate cancer, with affectation to the cricoid cartilage and oral cavity, being the first case to have ever been reported in Mexico. A 68-year-old Mexican man was diagnosed with prostate cancer and cribriform architecture histology with low serum level of prostate-specific antigen, debuting with laryngeal stridor. The biopsy came back positive for metastatic prostate carcinoma. During treatment with radiotherapy, metastasis developed to the oral cavity.